The middle to late Eocene greenhouse climate modelled using the CESM 1.0.5 - Baatsen, Michiel; von der Heydt, Anna S.; Huber, Matthew; Kliphuis, Michael A.; Bijl, Peter K.; Sluijs, Appy; Dijkstra, Henk A. (Climate of the past, 2020)
The early and late Eocene have both been the subject of many modelling studies, but few have focused on the middle Eocene. The latter still holds many challenges for climate modellers but is also key to understanding the events leading towards the conditions needed for Antarctic glaciation at the Eocene–Oligocene transition. Here, we present the results of CMIP5-like coupled climate simulations using the Community Earth System Model (CESM) version 1. Using a new detailed 38 Ma geography reconstruction and higher model resolution compared to most previous modelling studies and sufficiently long equilibration times, these simulations will help to further understand the middle to late Eocene climate. At realistic levels of atmospheric greenhouse gases, the model is able to show overall good agreement with proxy records and capture the important aspects of a warm greenhouse climate during the Eocene. With a quadrupling of pre-industrial concentrations of both CO2 and CH4 (i.e. 1120 ppm and ∼2700 ppb, respectively, or 4 × PIC; pre-industrial carbon), sea surface temperatures correspond well to the available late middle Eocene (42–38 Ma; ∼ Bartonian) proxies. Being generally cooler, the simulated climate under 2 × PIC forcing is a good analogue for that of the late Eocene (38–34 Ma; ∼ Priabonian). Terrestrial temperature proxies, although their geographical coverage is sparse, also indicate that the results presented here are in agreement with the available information. Our simulated middle to late Eocene climate has a reduced Equator-to-pole temperature gradient and a more symmetric meridional heat distribution compared to the pre-industrial reference. The collective effects of geography, vegetation, and ice account for a global average 5–7 ∘C difference between pre-industrial and 38 Ma Eocene boundary conditions, with important contributions from cloud and water vapour feedbacks. This helps to explain Eocene warmth in general, without the need for greenhouse gas levels much higher than indicated by proxy estimates (i.e. ∼500–1200 ppm CO2) or low-latitude regions becoming unreasonably warm. High-latitude warmth supports the idea of mostly ice-free polar regions, even at 2 × PIC, with Antarctica experiencing particularly warm summers. An overall wet climate is seen in the simulated Eocene climate, which has a strongly monsoonal character. Equilibrium climate sensitivity is reduced (0.62 ∘C W−1 m2; 3.21 ∘C warming between 38 Ma 2 × PIC and 4 × PIC) compared to that of the present-day climate (0.80 ∘C W−1 m2; 3.17 ∘C per CO2 doubling). While the actual warming is similar, we see mainly a higher radiative forcing from the second PIC doubling. A more detailed analysis of energy fluxes shows that the regional radiative balance is mainly responsible for sustaining a low meridional temperature gradient in the Eocene climate, as well as the polar amplification seen towards even warmer conditions. These model results may be useful to reconsider the drivers of Eocene warmth and the Eocene–Oligocene transition (EOT) but can also be a base for more detailed comparisons to future proxy estimates.